The impact of radioactive iodine treatment on subclinical left ventricular dysfunction in patients treated for differentiated thyroid cancer: assessing the predictive value of presystolic wave - Vural, Asli; Dikbas, Oguz; Vural, Selahattin; Bozoğlan, Hümeyra; Sönmez, Bircan (The European Research Journal, 2023)
Objectives: Despite strong evidence regarding the impact of radioactive iodine (RAI) on the hematopoietic, genitourinary, and gastrointestinal systems, its role in the cardiovascular system needs to be clarified. We hypothesized that the presence of a presystolic wave could be predictive for cardiovascular dysfunction in subjects receiving RAI. Thus, we investigated presystolic wave presence in differentiated thyroid cancer (DTC) patients with and without RAI therapy after undergoing total thyroidectomy. Methods: Patients were included in the study within 1-5 years after thyroidectomy or thyroidectomy and RAI treatment. Participants were divided into three groups as follows: the first group included patients with DTC who received RAI following total thyroidectomy (Group 1; n = 33), the second group included patients with DTC who did not receive RAI following total thyroidectomy (Group 2; n = 34). The third group of age-matched subjects who underwent total thyroidectomy with suspicion of DTC and resulted in benign pathologies was also selected (Group 3; n = 37). All subjects underwent transthoracic echocardiography. The presence of a presystolic wave was assessed with Doppler imaging of the left ventricular outflow tract. Results: Presystolic wave was more common in subjects receiving RAI (Group 1) compared to Group 2 (those without RAI) (90.9% vs. 61.8% respectively, p = 0.003), and its prevalence in Group 3 was 54.1%. Multiple logistic regression analysis revealed that receiving RAI (OR: 4.922, 95% CI: 1.640 – 20.022, p = 0.004) was independently associated with a 5-fold higher risk for the presence of a presystolic wave. Conclusions: RAI following total thyroidectomy in patients with DTC is associated with a five-fold increase in the presence of the presystolic wave, as a proxy marker for subclinical left ventricular dysfunction.